Development and Validation of a Prognostic Model for Post-Operative Recurrence of Pituitary Adenomas - Lu, Liang; Wan, Xueyan; Xu, Yu; Chen, Juan; Shu, Kai; Lei, Ting (Frontiers in Oncology, 2022)
Background: To predict postoperative recurrence in patients with pituitary adenomas (PAs) who achieved gross-total resection (GTR), we aimed to assess clinical factors associated with tumor recurrence and build a nomogram based on identified risk factors. Methods: A total of 829 patients with PAs who achieved GTR at Tongji Hospital between January 2013 and December 2018 were included in this retrospective study. The median follow-up time was 66.7 months (range: 15.6–106.3 months). Subjects were randomly divided into training (n = 553) or validation (n = 276) cohorts. A range of clinical characteristics, radiological findings, and laboratory data were collected. Uni- and multivariate Cox regression analyses were applied to determine the potential risk factors for PA recurrence. A nomogram model was then built to predict recurrence using the identified factors. Concordance index (C-index), calibration curve and receiver operating characteristic (ROC) were used to determine the predictive accuracy of the nomogram. Decision curve analysis (DCA) was performed to evaluate the clinical efficacy of the nomogram. Results: Pseudocapsule-based extracapsular resection (ER), cavernous sinus invasion (CSI) and tumor size were included in the nomogram. C-indices of the nomogram were 0.776 (95% confidence interval [CI]: 0.747–0.806) and 0.714 (95% CI: 0.681–0.747) for training and validation cohorts, respectively. Area under the curve (AUC) of the nomogram were 0.770, 0.774 and 0.818 for 4-, 6-, 8-year progression-free survival (PFS) probabilities in the training cohort, respectively; 0.739, 0.715 and 0.740 for 4-, 6-, 8-year PFS probabilities in the validation cohort, respectively. Calibration curves were well fitted in both training and validation cohorts. DCA revealed that the nomogram model improved the prediction of PFS in both cohorts. Conclusions: Pseudocapsule-based ER, CSI, and tumor size were identified as independent predictors of PA recurrence. In the present study, we developed a novel and valid nomogram with potential utility as a tool for predicting postoperative PA recurrence. The use of the nonogram model can facilitate the tailoring of counseling to meet the individual needs of patients.